Automated deduction - CADE-23 23rd International Conference on Automated Deduction, Wrocław, Poland, July 31 - August 5, 2011. Proceedings - Bjørner, Nikolaj; Sofronie-Stokkermans, Viorica (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 23rd International Conference on Automated Deduction, CADE-23, held in Wroclaw, Poland, in July/August 2011. The 28 revised full papers and 7 system descriptions presented were carefully reviewed and selected from 80 submissions. Furthermore, four invited lectures by distinguished experts in the area were included. Among the topics addressed are systems and tools for automated reasoning, rewriting logics, security protocol verification, unification, theorem proving, clause elimination, SAT, satifiability, interactive theorem proving, theory reasoning, static analysis, decision procedures, etc
Electronic reproduction.
Keywords: Computer science; Software engineering; Automatic theorem proving -- Congresses; Logic, Symbolic and mathematical -- Congresses; Automatic theorem proving; Electronic books